Discovery of T Cell Receptor β Motifs Specific to HLA–B27–Positive Ankylosing Spondylitis by Deep Repertoire Sequence Analysis. Issue 4 (29th March 2017) - Faham, Malek; Carlton, Victoria; Moorhead, Martin; Zheng, Jianbiao; Klinger, Mark; Pepin, Francois; Asbury, Thomas; Vignali, Marissa; Emerson, Ryan O.; Robins, Harlan S.; Ireland, James; Baechler‐Gillespie, Emily; et al.
Abstract : Objective: Ankylosing spondylitis (AS), a chronic inflammatory disorder, has a notable association with HLA–B27. One hypothesis suggests that a common antigen that binds to HLA–B27 is important for AS disease pathogenesis. This study was undertaken to determine sequences and motifs that are shared among HLA–B27–positive AS patients, using T cell repertoire next‐generation sequencing. Methods: To identify motifs enriched among B27‐positive AS patients, we performed T cell receptor β (TCRβ) repertoire sequencing on samples from 191 B27‐positive AS patients, 43 B27‐negative AS patients, and 227 controls, and we obtained >77 million TCRβ clonotype sequences. First, we assessed whether any of 50 previously published sequences were enriched in B27‐positive AS patients. We then used training and test cohorts to identify discovered motifs that were enriched in B27‐positive AS patients versus controls. Results: Six previously published and 11 discovered motifs were enriched in the B27‐positive AS samples as compared to controls. After combining motifs related by sequence, we identified a total of 15 independent motifs. Both the full set of 15 motifs and a set of 6 published motifs were enriched in the B27‐positive AS patients as compared to B27‐positive healthy individuals ( P = 0.049 and P = 0.001, respectively). Using an independent cohort, we validated that at least some of these motifs were associated with AS, and not simply with B27‐positive status. Conclusion: We identified TCRβ motifs that are enriched in B27‐positive AS patients as compared to B27‐positive healthy controls. This suggests that a common antigen, presented by HLA–B27 and detected by CD8+ T cells, may be associated with AS disease pathogenesis.